Identification of a ligand-binding site on tubulin mediating the tubulin–RB3 interaction - Yong Li; Chufeng Zhang; Dongmei Tang; Tao Wang; Wei Yan; Linyu Yang; Peng Bai; Minghai Tang; Heying Pei; Lijuan Chen; Qiang Chen; Jianhong Yang (Proceedings of the National Academy of Sciences, 2025)
For decades, microtubules—composed of αβ-tubulin dimers—have been primary targets for cancer chemotherapy. While eight binding sites on the tubulin dimer have been structurally characterized, this study reveals a ninth. We found that the tubulin inhibitor Tumabulin-1 (TM1, a BML284 derivative) binds simultaneously to the well-known colchicine site and a previously unknown site, designated as Tumabulin site. This site resides at the interface of α1-tubulin, β1-tubulin, and RB3 within the tubulin–RB3–tubulintyrosine ligase complex. Remarkably, two TM1 molecules bind cooperatively to this relatively large pocket, interacting with all three proteins. Crucially, this binding is dependent on RB3; it is absent when RB3 is missing or the key residue H71 is mutated (H71Q). We further designed and synthesized Tumabulin-2 (TM2) that selectively binds the Tumabulin site, excluding binding the colchicine site. TM2 acts as a molecular glue, strengthening the interaction between RB3 and the tubulin dimer and consequently enhancing RB3’s tubulin-depolymerizing activity. In conclusion, our findings confirm the existence of a ninth tubulin-binding site and offer a promising foundation for developing Tubulin–RB3 molecular glues as a next generation of anticancer therapeutics.